PENDIDIKAN AGAMA ISLAM SEBAGAI UPAYA PENCEGAHAN RADIKALISME DI SEKOLAH - Farhan Maulana Arli (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
Religious radicalism among students is becoming an increasingly worrying phenomenon in the context of national education. Schools, as formal educational institutions, have the potential to become spaces for the formation of moderate or extreme religious values, depending on the educational patterns implemented. This study aims to analyze the role and function of Islamic Religious Education (PAI) as an instrument for preventing radicalism in schools. The method used was a literature review by reviewing relevant books, journal articles, and research reports. The results show that Islamic Religious Education plays a crucial role in internalizing the values ​​of religious moderation, such as tawasuth (moderation), tasamuh (tolerance), and tawazun (balance). PAI, developed through a humanistic, dialogical, and contextual approach, has been proven to strengthen a peaceful understanding of Islam and prevent the development of intolerant and radical attitudes among students. Therefore, strengthening the competence of Islamic Religious Education teachers, updating the curriculum based on religious moderation, and synergy between schools and the community are key to preventing radicalism through education.